Building probabilistic graphical models with Python : solve machine learning problems using probabilistic graphical models implemented in Python with real-world applications /: solve machine learning problems using probabilistic graphical models implemented in Python with real-world applications. (2014) - Karkera, Kiran R
No abstract available